Leadership now : reflections on the legacy of Boas Shamir - Katz, Israel, 1948-; Eilam-Shamir, Galit; Kark, Ronit; Berson, Yair (Emerald Publishing Limited, 2018)
The late Boas Shamir made a significant contribution to the development of novel theories and frameworks in the leadership field. He became one of the most influential figures in leadership research, and left behind him an outstanding body of work.'Leadership Now: Reflections on the Legacy of Boas Shamir' incorporates some of Boas Shamir's most classic and significant works, and includes contributions from a group that represent the most influential leaders in the field, up and coming scholars, as well as students of Boas Shamir. The first part of the book focuses on Shamirs most influential work on the motivational effects of charismatic leaders. The second part follows with work on the charismatic relationship; reflecting the shift of Boas Shamir's work in the later parts of his career from a leader-centric focus to a closer examination of the relational aspects of leadership and the major effects followers have on the leadership process. The third part includes samples of this work on the role of the contextual factors in leadership. This volume aims to preserve Boas Shamir's legacy and inspire further generations of leadership scholars.
Includes index.
Keywords: Leadership.; Shamir, Boas.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books